Consumer brand engagement and the continuance intention of online shopping users - Nazif Hardi; Astra Prima Budiarti (Operations Management and Information System Studies, 2023)
This study aims to analyze "The Effect of Consumer Brand Engagement on the Continuance Intention of Shopee Application Users". The population for this study only consisted of Shopee Application users, and the sample for this study was Shopee users in West Sumatra who used the Shopee Application at least once for online shopping. In this study, the number of samples is 200 respondents. Data collection was carried out through an online survey (google form) and managed using SmartPLS 4.0 software. The results of this study show that (1) cognitive processing has a positive and significant effect on the continuance intention of Shopee application users in West Sumatra. (2) affection has a positive and significant effect on the continuance intention of Shopee application users in West Sumatra. (3) activation has a positive and significant effect on the continuance intention of Shopee application users in West Sumatra. (4) cognitive processing has a positive and significant effect on the activation of Shopee application users in West Sumatra. (5) affection has a positive and significant effect on the activation of Shopee application users in West Sumatra. (6) cognitive processing has a positive and significant effect on continuance intention through activation as an intervening variable. (7) affection has a positive and significant effect on continuance intention through activation as an intervening variable.